How muftis think : Islamic legal thought and Muslim women in Western Europe - Larsen, Lena. (Studies in Islamic Law and Society, 2018)
In How Muftis Think Lena Larsen explores fatwas that respond to questions asked by Muslim women in Western Europe in recent decades. The questions show women to be torn between two opposing notions of morality and norms: one stressing women's duties and obedience, and one stressing women's rights and equality before the law. Focusing on muftis who see "the time and place" as important considerations in fatwa-giving, and seek to develop a local European Islamic jurisprudence on these increasingly controversial issues, Larsen examines how they deal with women's dilemmas. Careful not to suggest easy answers or happy endings, her discussion still holds out hope that European societies and Muslim minorities can recognize shared moral concerns.